2002
DOI: 10.1177/1359104502007001003
|View full text |Cite
|
Sign up to set email alerts
|

Children of Somatically Ill Parents: A Methodological Review

Abstract: A B S T R A C TThe children of seriously ill parents are at risk for emotional disturbances. This review covers five former reviews, three theoretical articles, five case studies and 39 sample studies from the last 15 years. Methodological problems and shortcomings of previously published studies are discussed in detail. Based on former reviews and theoretical approaches, a developmental framework for children's adaptation processes is elaborated. Empirical studies are analysed with a differentiation of how va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
79
0
10

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 42 publications
4
79
0
10
Order By: Relevance
“…Adolescents may report a higher level of maladjustment than younger children because they have a greater understanding of the risks and may be saddled with additional familial responsibilities (Romer et al, 2002;Stein, Riedel, & Rotheram-Borus, 1999). A socially stigmatized illness such as HIV/AIDS may present a heightened level of familial stress that negatively impacts youths' adjustment, particularly when coupled with maternal substance abuse and persistent poverty (Pequegnat & Bray, 1997).…”
Section: The Additional Burden Of Maternal Hiv-infectionmentioning
confidence: 99%
“…Adolescents may report a higher level of maladjustment than younger children because they have a greater understanding of the risks and may be saddled with additional familial responsibilities (Romer et al, 2002;Stein, Riedel, & Rotheram-Borus, 1999). A socially stigmatized illness such as HIV/AIDS may present a heightened level of familial stress that negatively impacts youths' adjustment, particularly when coupled with maternal substance abuse and persistent poverty (Pequegnat & Bray, 1997).…”
Section: The Additional Burden Of Maternal Hiv-infectionmentioning
confidence: 99%
“…Die Diagnose einer ernsthaften oder gar lebensbedrohlichen Erkrankung, wie beispielsweise Krebs, Multipler Sklerose, AIDS oder dialysepflichtiger Niereninsuffizienz kann bei bislang gesunden Eltern zu einer tiefgreifenden Erschütterung des eigenen Selbstbildes von Unversehrtheit und vitaler Kraft führen (Frick-Bruder, 1998). Mit der Krankheit assoziierte Stressoren wie häufige medizinische Eingriffe, Krankenhausaufenthalte, Veränderungen des körperlichen Erscheinungsbildes und gegebenenfalls die Auseinandersetzung mit einer vitalen Bedrohung werden von allen Familienangehörigen miterlebt (Worsham, Compas, Sydney, 1997;Christ, 2000a;Romer et al, 2002b (Romer et al, 2006). Viele Kinder reagieren auf die von ihnen erfühlten Belastungen der Eltern, indem sie sich von ihrer stärksten Seite zeigen und ihre eigenen Sorgen von den Eltern fernhalten.…”
Section: Introductionunclassified
“…Dies kann aus verhaltensbiologischer Sicht als eine sinnvolle Priorisierung der Gefährdung des eigenen Organismus bzw. seiner Genesung verstanden werden (Romer, Schulte-Markwort, Riedesser, 2002a). Die Legitimation des Bedürfnisses, die eigene Stabilisierung in den Vordergrund zu stellen, ist daher ein wohlbegründetes Element psychosozialer Betreuungskonzepte für körperlich kranke Erwachsene.…”
Section: Introductionunclassified
“…Although the emotional impact of cancer on families is clearly documented in relation to partners (Zahlis and Shands, 1991;Glasdam et al, 1996;Baider et al, 1998;Northouse et al, 1998) and adult children (Rait and Lederberg, 1989;Edwards and Clarke, 2004), the evidence for school age children is less clear (Romer et al, 2002). Several studies have reported that children of mothers with breast cancer exhibit a high rate of psychological and behavioural disturbance (Wellisch et al, 1992;Compas et al, 1994;Welch et al, 1996;Birenbaum et al, 1999;Nelson and While, 2002).…”
mentioning
confidence: 99%